Sorological evaluation of commercial vaccines against enterotoxemia in goats. - VESCHI, J. L. A. (2008)
Enterotoxemia in sheep and in goats is caused by the effects of the epsilon toxin of C/ostridium perfringens type D, being considered the main infectious cause of mortality in those animal species. The main prophylactic measures include adequate nutritional management and vaccination of ali animais using vaccines of high immunogenic power. Six commercial vaccines containing in its formulation the epsilon toxoid of C. perfringens type D were sorogically evaluated. Eighty four female goat kids, whose mothers had no previous vaccination history against clostridioses were used. They were divided into six groups of 14 animais each. The animais of the control group didn't receive any vaccine dose and the animais from the groups 1 to 5 received two vaccine doses, The first vaccine dose was applied at 45 days of life (day zero) and the second dose at 75 days (30 days after the first dose). Blood samples were collected from the goat kids at the days zero, 30, 60, 90, 120 and 150 after the beginning of the experiment, in order to evaluate the immunologic response. The Indirect ELlSA technique was used for the quantification of the antibodies against epsilon toxin in the samples of blood serum of the animais. In day zero, no animal presented titre considered protector. The largest number of animais considered protected was found at day 60, in response to the two initial doses of the vaccine (days O and 30, first and second doses, respectively). Only tive animaIs which received the vaccine 1 and one animal which received the vaccine 3 stayed wilh titres of antibodies considered up to 150 days after the first vaccine dose. Based on the results, it was concluded lhat the evaluated vaccines showed small amount of epsilon toxoid in the commercial formulations, a crucial fact for lhe low efficiency of. the vaccines. For commercial reasons, the vaccines against the clostridioses present versatile formulations, with several toxoid types, used for various animal species, which certainly contributed to reduce their effectiveness in preventing the iIInesses caused by the clostridia or their toxins.